9×(8-6)= (17+25):7= 100-(56+18)= 85-39+17= 35:(45-38)= 4×(81:9)= 86-(29+19)= 49:7×9= 6×9+37=; 72:8:3= 17 ×7×7= 100-64+38=
Răspunsuri la întrebare
Răspuns de
2
Explicație pas cu pas:
9×(8-6)=9×2=18
(17+25):7=42:7=6
100-(56+18)=100-74=26
85-39+17=46+17=63
35:(45-38)=35:7=5
4×(81:9)=4×9=36
86-(29+19)=86-48=38
49:7×9=7×9=63
6×9+37=54+37=91
72:8:3=9:3=3
17×7×7=119×7=833
100-64+38=36+38=74
Răspuns de
1
Explicație pas cu pas:
9×(8-6)=9×2=18
(17+25)÷7=42÷7=6
100-(56+18)=100-74=26
85-39+17=102-39=63
35÷(45-38)=35÷7=5
4×(81÷9)=4×9=36
86-(29+19)=86-49=38
49÷7×9=7×9=63
6×9+37=54+37=91
72÷8÷3=9÷3=3
17×7×7=17×7²=17×49=833
100-64+38=100-102=-2
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă